2002
DOI: 10.1046/j.1365-3156.2002.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and use of prevention measures related to dengue in northern Thailand

Abstract: Summaryobjective To determine the frequency and determinants of knowledge of dengue infection in three sites in northern Thailand, and to compare prevention measures of people with and without knowledge of dengue.methods In May 2001 we conducted an epidemiological survey among 1650 persons living in three areas in northern Thailand. Knowledge of dengue and the use of prevention measures were measured by means of a structured questionnaire. Differences in knowledge of dengue and the use of prevention measures b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
83
5
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 6 publications
(6 reference statements)
25
83
5
4
Order By: Relevance
“…10 Bota et al found that ages ranged from 17-29 years. This was contrast to our study where majority (63%) were between 25-40 years 12 In our study, out of 200 respondents, 80 (40%) were graduates, 42 (21%) were postgraduates, 32 (16%) had their education till 12 th standard, 20 (10%) were illiterate, 20 (10%) had their education till 10 th standard while 6 (3%) respondents had their education of primary level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Bota et al found that ages ranged from 17-29 years. This was contrast to our study where majority (63%) were between 25-40 years 12 In our study, out of 200 respondents, 80 (40%) were graduates, 42 (21%) were postgraduates, 32 (16%) had their education till 12 th standard, 20 (10%) were illiterate, 20 (10%) had their education till 10 th standard while 6 (3%) respondents had their education of primary level.…”
Section: Discussionmentioning
confidence: 99%
“…9 Benthem claimed that people with higher knowledge on dengue reported a higher use of preventive measure than people with low knowledge. 10 Preventive measures for dengue fever are mosquito bed net, repellent cream on the skin, wearing long sleeves and pants for additional protection, window and door screens and air-conditioning.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies recommend that better knowledge of dengue leads to better prevention techniques adopted by people to prevent dengue. It is reported that people having high level of knowledge regarding dengue, use better prevention practices in order to avoid dengue [7,8]. Begonia et al [9], conducted a study to know knowledge of people about dengue fever.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, Al-Dubai et al 11 and Juni et al 12 did not reveal any association between ethnicity and dengue preventive behaviour. Findings regarding the association of dengue preventive behavior with age and income level are also conflicting [12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaires used in the studies differed greatly from each other. Thus, in some studies, the dengue knowledge component of the questionnaire included questions on disease transmission and dengue signs and symptoms 14 while others focused exclusively on mosquito biting and breeding habits 18,19 . Several studies reported that they applied convenience sampling 11,16,20 , and some studies did not specify a sampling method 12,14 , which might have compromised the generalizability of the findings.…”
Section: Introductionmentioning
confidence: 99%